Ageism and caring attitudes among nurses in oncology. (16th December 2015) - Schroyen, S.; Missotten, P.; Jerusalem, G.; Gilles, C.; Adam, S.
ABSTRACT: Background: Although the incidence of cancer increases with age, elderly patients are often excluded from clinical trials. In addition, elderly patients are frequently undertreated in comparison to younger patients. One explanation for these observations is age stigma (i.e. ageism). In this context, this study has two objectives: (1) to replicate the results of previous studies that reported differential support of medical treatment depending on the patient's age in a different healthcare provider population (nurses rather than physicians); and (2) to determine whether support for expensive immunotherapy, adjuvant chemotherapy, or breast reconstruction is linked to ageism among nurses. Method: The participants were 76 nurses who specialized in oncology. They received four clinical vignettes: one vignette about an immunotherapy with a high societal cost (age of patient: 40 vs. 70 years), and three vignettes about adjuvant chemotherapy and breast reconstruction (age of patient: 35, 55, or 75 years – age was the only difference). A questionnaire and a fluency task were used to assess the participants' vision of aging. Results: Our analyses show that support for immunotherapy, breast reconstruction, and chemotherapy is lower for older patients than for younger patients. Moreover, nurses' vision of aging influences support for breast reconstruction: nurses with a negative view of age discriminated more between a 75-year-old patient and a 35-year-old patient (less encouragement for the older patient). Conclusion: These results highlight the need for nurses and other healthcare providers to receive specific training about ageism and its consequences.